The influence of interstitial cells of Cajal loss and aging on slow wave conduction velocity in the human stomach. Issue 24 (23rd December 2020) - Wang, Tim Hsu‐Han; Angeli, Timothy R.; Ishida, Shunichi; Du, Peng; Gharibans, Armen; Paskaranandavadivel, Niranchan; Imai, Yohsuke; Miyagawa, Taimei; Abell, Thomas L.; Farrugia, Gianrico; Cheng, Leo K.; O'Grady, Gregory
Abstract: Loss of interstitial cells of Cajal (ICC) has been associated with gastric dysfunction and is also observed during normal aging at ~13% reduction per decade. The impact of ICC loss on gastric slow wave conduction velocity is currently undefined. This study correlated human gastric slow wave velocity with ICC loss and aging. High‐resolution gastric slow wave mapping data were screened from a database of 42 patients with severe gastric dysfunction ( n  = 20) and controls ( n  = 22). Correlations were performed between corpus slow wave conduction parameters (frequency, velocity, and amplitude) and corpus ICC counts in patients, and with age in controls. Physiological parameters were further integrated into computational models of gastric mixing. Patients : ICC count demonstrated a negative correlation with slow wave velocity in the corpus (i.e., higher velocities with reduced ICC; r 2  = .55; p  = .03). ICC count did not correlate with extracellular slow wave amplitude ( p  = .12) or frequency ( p  = .84). Aging : Age was positively correlated with slow wave velocity in the corpus (range: 25–74 years; r 2  = .32; p  = .02). Age did not correlate with extracellular slow wave amplitude ( p  = .40) or frequency ( p  = .34). Computational simulations demonstrated that the gastric emptying rate would increase at higher slow wave velocities. ICC loss and aging are associated with a higher slow wave velocity. The reason for these relationships is unexplained and merit further investigation. Increased slow wave velocity may modulate gastric emptying higher, although in gastroparesis other pathological factors must dominate to prevent emptying. Abstract : Loss of interstitial cells of Cajal and aging is associated with a higher gastric slow wave velocity. This study used human data for correlation and computational models to determine the effects on gastric emptying and mixing. The reason for these relationships is unexplained and merit further investigation.